Acute Cerebellar Ataxia As A Parotitis Complication: Clinical Evaluation And Management - OKKY PRASETYO; ERNY PRASETYO; DENNY PRASETYO (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Acute cerebellar ataxia is a motor control or coordination disorder that can be caused by several things, most often in children due to viral infections including paramyxovirus, head trauma, stroke and intoxication with varying prognosis. The paramyxovirus causes parotitis is highly neurotrophic with aseptic meningitis, encephalitis, hydrocephalus, decreased blood flow on the cerebellum and vasculitis. Those mechanisms implicated on many clinical symptoms, including cerebellar ataxia. Management is only limited to supportive and rehabilitative because symptoms will improve within 2-3 weeks